Akibat Hukum Kontrak (Akad) Terhadap Subjek dan Objeknya - Muslih Muslih (UIN Sunan Kalijaga Yogyakarta, 2018)
The agreement is a legal relationship regarding the ties between parties that cause legal consequences and must be fulfilled. In classical fiqh, agreements only involve parties who make and do not apply to other parties. However, at certain limits due to contract law it can also involve third parties. With respect to the object of the contract, transfer of ownership can be carried out if the provisions in the form of the scope of the contents of the agreement, the binding capacity of the agreement and the responsibilities of the agreement have been fulfilled.